Diatom Nitzschia navis-varingica (Bacillariophyceae) and its domoic acid production from the mangrove environments of Malaysia - Tan, Suhnih; Teng, Singtung; Lim, Hong Chang; Kotaki, Yuichi; Bates, Stephen S.; Leaw, Chui Pin; Lim, Po Teen (Elsevier B.V., 2016)
The distribution of the toxic pennate diatom Nitzschia was investigated at four mangrove areas along the coastal brackish waters of Peninsular Malaysia. Eighty-two strains of N. navis-varingica were isolated and established, and their identity confirmed morphologically and molecularly. Frustule morphological characteristics of the strains examined are identical to previously identified N. navis-varingica, but with a sightly higher density of the number of areolae per 1 μm (4–7 areolae). Both LSU and ITS rDNAs phylogenetic trees clustered all strains in the N. navis-varingica clade, with high sequence homogeneity in the LSU rDNA (0–0.3%), while the intraspecific divergences in the ITS2 data set reached up to 7.4%. Domoic acid (DA) and its geometrical isomers, isodomoic A (IA) and isodomoic B (IB), were detected in cultures of N. navis-varingica by FMOC-LC-FLD, and subsequently confirmed by LC–MS/MS, with selected ion monitoring (SIM) and multiple reaction monitoring (MRM) runs. DA contents ranged between 0.37 and 11.06 pg cell−1. This study demonstrated that the toxigenic euryhaline diatom N. navis-varingica is widely distributed in Malaysian mangrove swamps, suggesting the risk of amnesic shellfish poisoning and the possibility of DA contamination in the mangrove-related fisheries products